2005
DOI: 10.1027/1614-0001.26.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Ability and Self-Reported Efficacy of Self-Presentation Predict Faking on Personality Measures

Abstract: Abstract. The main aim of the present study was to investigate whether faking on personality measures is predicted by cognitive ability and self-reported efficacy of positive self-presentation (ESP) assessed under honest conditions. 123 participants completed the NEO Five Factor Inventory (NEO-FFI) and the self-deceptive enhancement (SDE) and impression management (IM) scales of the Balanced Inventory of Desirable Responding Version 7 (BIDR) under four instructional sets: honest, fake bad, fake good, and two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 41 publications
4
58
0
1
Order By: Relevance
“…Similarly, when a job indicated that lower scores on certain traits might be better, higher EI was associated with stronger effects in that direction. The nature of the effects and the effect sizes were roughly in line with those found for other traits known to be related to the ability to fake, such as openness (Raymark & Tafero, 2009), integrity (McFarland & Ryan, 2000, and efficacy of self-presentation (Pauls & Crost, 2005). In addition, trait EI showed incremental validity over GMA and the Big Five personality dimensions in its relation with the ability to fake.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Similarly, when a job indicated that lower scores on certain traits might be better, higher EI was associated with stronger effects in that direction. The nature of the effects and the effect sizes were roughly in line with those found for other traits known to be related to the ability to fake, such as openness (Raymark & Tafero, 2009), integrity (McFarland & Ryan, 2000, and efficacy of self-presentation (Pauls & Crost, 2005). In addition, trait EI showed incremental validity over GMA and the Big Five personality dimensions in its relation with the ability to fake.…”
Section: Discussionsupporting
confidence: 78%
“…They found that the produced personality profiles differed considerably between the two conditions. Although they were not the first to discover that differential instructional sets result in different personality profiles (Furnham, 1990;Mahar, Colognon, & Duck, 1995;Martin, Bowen, & Hunt, 2002;Pauls & Crost, 2005), they concluded, "Further research is needed, examining a number of different jobs, to determine whether individual differences in ability to fake toward a job are stable across jobs" (p. 101). The present study directly addresses this question by using a within-subject design to investigate faking toward two very distinctive jobs and the role of trait EI in doing so.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Yine işe alınacak kişilere uygulanan ve işe alım görüşmelerinde aldatma davranışına benzeyen, kişilik testlerinde aldatma davranışı hakkında da birçok araştırma mevcuttur (Arthur, Woehr ve Graziano, 2001;Birkeland, Manson, Kisamore, Brannick ve Smith, 2006;Christiansen, Goffm, Johnston ve Rothstein, 1994;Dalen, Stanton ve Roberts, 2001;Goffin ve Christiansen, 2003;Furnham, 1990;Heggestad, Morrison, Charlie, McCloy, 2006;Hogan, Barrett ve Hogan, 2007;Holden ve Hibbs, 1995;Jackson, Wroblewski ve Ashton, 2000;Luther ve Thornton III, 1999;Mahar, Cologon ve Duck, 1995;Pauls ve Crost, 2005;Rothstein ve Goffin, 2006;Rosse, Stecher, Miller ve Levin, 1998;Schmitt ve Oswald, 2006;Ones ve Viswesvaran, 1998;Van Hooft ve Born, 2012).…”
Section: İşe Alım Görüşmesinde Aldatma Davranışıunclassified